(untitled) (Research, Society and Development, 2023)
Breastfeeding is an extremely important practice for the infant’s first physiological needs, bringing benefits and influencing a lifetime. It is an aid factor in the child’s facial development, in addition to directly interfering with the risks of diseases such as: hypertension, hypercholesterolemia, obesity and diabetes, it is also worth remembering its performance in the immune system, preventing the incidence of infectious diseases. The study aims to analyze and encourage breastfeeding in children with cleft lip and palate, showing the different methods so that the practice can happen and that it is beyond nutrition, a unique experience of love for the mother and the newborn, being able to overcome the difficulties encountered during the period. The study is a literature review based on scientific articles researched and found on different digital platforms. The main results are early weaning and lack of encouragement and guidance for mothers who wish to breastfeed their newborns, which can generate different frustrations for the woman and nutritional deficiencies for the child. It appears that the practice of exclusive breastfeeding in children who have this congenital malformation is possible and very important, also depending on the preparation of the multidisciplinary team that supports and assists the mother and child in this process, with encouragement and guidance necessary for breastfeeding to happen in a healthy way and the lack of it does not bring harm to the health of the binomial.